Proportions of maxillary anterior teeth relative to each other and to golden standard in Chitwan Medical College - Mishra, Meena Kumari; Guragain, Manjeev; Thakur, Smriti Narayan; Chaudhary, Sanjeeb (Journal of Chitwan Medical College, 2018)
Introduction: One of the most important aspects of aesthetic dentistry while restoring or replacing maxillary anterior teeth is the creation of harmonious proportion between the widths of them. The appearance of anterior teeth is critical for an attractive face and pleasing smile. The dimensional determination of maxillary anterior teeth is an important factor for both, esthetic and function. Materials and Methods: This study was conducted in 140 dentate subjects. Out of the 140 subjects, 70 (50%) were males and 70 (50%) were females. The age of the patients in this study ranged from 18 to 50 years. Maxillary impressions of selected subjects were made with an irreversible hydrocolloid impression material. The mesiodistal width of the maxillary anterior teeth was measured from the casts with a Boley gauge. Results: The mean width ratios were 0.83 for right LI/CI and 0.85 for left LI/CI, 1.12 for right CN/LI and 1.1 for left CN/LI in total population. The mean width ratios in male group were 0.83 for right LI/CI and 0.87 for left LI/CI, 1.14 for right CN/ LI and 1.1 for left CN/LI. Similarly, in female group the mean width ratios were 0.82 for right LI/CI and 0.83 for left LI/CI, 1.1 for right CN/LI and 1.1 for left CN/LI. Conclusion: In the evaluation of LI/CI, CN/LI, WLRs golden proportion was not found in left and right for both sexes.